2015
DOI: 10.1007/s10797-015-9349-0
|View full text |Cite
|
Sign up to set email alerts
|

Personal taxation of capital income and the financial leverage of firms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…One obvious shifting possibility is an increase in the leverage ratio of privately owned firms: for non-listed Norwegian firms Alstadsaeter and Fjaerli (2009) find strong timing effects of dividends prior to and a reduced leverage ratio after an increase in the tax rate on dividends. For the German withholding tax reform, Fossen and Simmler (2015) find that leverage at the unincorporated firm level increased in reaction to the decreased marginal tax rate on interest income, but only to a small degree. This comparatively small effect in Germany might be a consequence of restricted applicability of the reduced tax rate on interest income for loans between family members, firm owners and firm, and similar cases (see §32d EStG) as it impedes shifting from business profits (both incorporated and other) to interest income.…”
Section: Shifting Evasion and Real Responsesmentioning
confidence: 91%
“…One obvious shifting possibility is an increase in the leverage ratio of privately owned firms: for non-listed Norwegian firms Alstadsaeter and Fjaerli (2009) find strong timing effects of dividends prior to and a reduced leverage ratio after an increase in the tax rate on dividends. For the German withholding tax reform, Fossen and Simmler (2015) find that leverage at the unincorporated firm level increased in reaction to the decreased marginal tax rate on interest income, but only to a small degree. This comparatively small effect in Germany might be a consequence of restricted applicability of the reduced tax rate on interest income for loans between family members, firm owners and firm, and similar cases (see §32d EStG) as it impedes shifting from business profits (both incorporated and other) to interest income.…”
Section: Shifting Evasion and Real Responsesmentioning
confidence: 91%
“…To tackle the problem of the identification of the marginal owner when using investor level tax rates, several studies proxy for firm-specific ownership (Lin and Flannery 2013; Faccio and Xu 2015) or use data on observed ownership structures (Fossen and Simmler 2016; Babbel et al 2018). Similar to Babbel et al (2018), our dataset allows us to directly observe the composition of the firm-specific ownership structure and thus the marginal owner of the firm.…”
Section: Net Tax Benefit Of Debt and Institutional Backgroundmentioning
confidence: 99%
“…We use WhollyOwn, as Jiang et al (2017) have shown that firms that are controlled by one single owner have the lowest agency costs and thus the most effective ownership structure. Alternatively, we follow Fossen and Simmler (2016) and use MajOwn to control for the effect of taxes in the presence of a majority owner and we follow Pindado and de la Torre (2011) and Babbel et al (2018) who define the marginal owner of the firm as the largest owner LargeOwn .…”
Section: Data and Regression Modelmentioning
confidence: 99%